Sound For Film And Television / Tomlinson Holman - Holman, Tomlinson
Sound for Film and Television, Third Edition provides a thorough introduction to the fascinating field of recording, editing, mixing, and exhibiting film and television sound. It strikes a fine balance between aesthetic and technical content, combining theory and practice to approach sound as both an art and a science. This new edition has been completely updated to reflect the latest advances in HD technology, new hardware and software systems, new distribution methods, wireless sound capture, and more. Also, analog-related content has been reduced and transferred.